2016
DOI: 10.1007/s11356-016-7754-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from plant seed oils as an alternate fuel for compression ignition engines—a review

Abstract: The modern scenario reveals that the world is facing energy crisis due to the dwindling sources of fossil fuels. Environment protection agencies are more concerned about the atmospheric pollution due to the burning of fossil fuels. Alternative fuel research is getting augmented because of the above reasons. Plant seed oils (vegetable oils) are cleaner, sustainable, and renewable. So, it can be the most suitable alternative fuel for compression ignition (CI) engines. This paper reviews the availability of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…The pequi fruit (Caryocar brasiliensis, also known as souari nut) is used in many different ways (Ferreira et al, 2017), including consumption human food, as a component of commercial animal food, and in folk medicine (for a thorough review, see Almeida and Silva, 1994). The pequi also exhibits the potential to be used in biodiesel production, due to a large number of oil components in its fruits (Mujeeb et al, 2016;Vijayakumar et al, 2016). Despite of its importance, this species is affected by the low dispersal rates of their seeds.…”
Section: (With 1 Figure)mentioning
confidence: 99%
“…The pequi fruit (Caryocar brasiliensis, also known as souari nut) is used in many different ways (Ferreira et al, 2017), including consumption human food, as a component of commercial animal food, and in folk medicine (for a thorough review, see Almeida and Silva, 1994). The pequi also exhibits the potential to be used in biodiesel production, due to a large number of oil components in its fruits (Mujeeb et al, 2016;Vijayakumar et al, 2016). Despite of its importance, this species is affected by the low dispersal rates of their seeds.…”
Section: (With 1 Figure)mentioning
confidence: 99%
“…Based on the insecticidal property's neem is widely used in most part of Asia as a traditional remedy against maggots and head lice [30]. In Haiti, studies have shown that, crushed leaves, decoctions, are rubbed into open wounds and injured cuts [11,66].…”
Section: Dermatological Insectsmentioning
confidence: 99%
“…Using large volumes of petroleum derivatives like diesel causes them to go extinct in the next [30][31][32][33][34][35][36][37][38][39][40] years. Because of their high thermal e ciency, diesel engines have an extensive choice of uses in the transportation industry (Vijayakumar et al 2016). According to the studies (Ramakrishnan et al 2018; Sharma and Duraisamy 2019; Ulusoy 2020; Chatterjee et al 2021), India is one of the major oil importers and consumers.…”
Section: Introductionmentioning
confidence: 99%